A rare case of gingival metastases from papillary thyroid carcinoma. (2015) - Siddique, Ibraz; Chengot, Preetha; Frewer, John; Walker, David
Highlights: The attached gingiva is a rare site for metastasis in the oral cavity. Metastasis to the oral cavity usually indicates disseminated malignant disease. Clinicians must be vigilant when presented with an oral soft tissue mass in patients with a known underlying malignancy. There should be a low threshold to biopsy gingival lesions in patients with a history of carcinoma. Early identification of distant metastases in the oral cavity is important in planning appropriate and timely palliative management. Abstract: Metastatic oral malignancy accounts for 1% of all oral cancers. Oral soft tissue involvement is rare and accounts for less than 0.1% of all oral tumours with the attached gingiva being the commonest site affected. We present the first reported case of a papillary thyroid carcinoma (PTC) with sarcomatoid transformation giving rise to gingival metastasis. A 71 year old man with a history of PTC presented with an asymptomatic gingival swelling adjacent to his lower right lateral incisor. Subsequent biopsy of the lesion confirmed PTC metastasis with aggressive sarcomatoid features. We present a clinical photograph of the gingival swelling and the pathology images demonstrating both the papillary and sarcomatoid features of the gingival biopsy. The prognosis of PTC is usually excellent but some histological variants of PTC behave more aggressively. The histology in our case demonstrated solid areas and sarcomatoid transformation and behaved far more aggressively than typical PTC. Sarcomatoid transformation in PTC has not been previously described and indicates a poor prognosis and the need for planning urgent palliation. These lesions can present a diagnostic challenge to both pathologists and clinicians in identifying the lesion as metastatic and locating the primary cancer. This case demonstrates the need for vigilance amongst health professionals when presented with an oral soft tissue mass in patients with a known primary malignancy. This may be the first evidence of disseminated disease and emphasises a low threshold to biopsy oral soft tissue lesions in patients with a history of malignant disease.